A Rare Case of Ibuprofen-Induced Eosinophilic Meningitis in a 13-Year-Old Girl. (January 2014) - Bansal, Sharad; Gupta, Mukesh; Sharma, Deepak; Bansal, Shweta
Eosinophilic meningoencephalitis is based on clinical manifestations and microscopic identification of eosinophils present in cerebrospinal fluid (CSF). It is caused by a variety of helminthic infections with most common being angiostrongyliasis, gnathostomiasis, toxocariasis, cysticercosis, schistosomiasis, baylisascariasis, and paragonimiasis. Many case reports are there in which parasites have been found responsible, but there are rare reports of CSF eosinophilia associated with the use of drugs. We report a case of drug-induced (ibuprofen) eosinophilic meningitis in a healthy female who presented to us with severe headache and improved dramatically after drug withdrawal.